Perancangan Baru Museum Tekstil Di Kota Bandung Dengan Pendekatan Interaktif Naratif - Faiz, Muhammad; Murdowo, Djoko; Cardiah, Tita (eProceedings of Art & Design, 2024)
The design of the Textile Museum in Bandung City aims to preserve and introduce Indonesia's cultural heritage, especially textile art, as an important part of the nation's cultural identity and wealth. This museum is an important forum for increasing cultural awareness, strengthening local identity, and developing the education, tourism and economic sectors of local communities. Against the background of decreasing interest in local culture, especially textile arts, due to the influence of globalization, it is hoped that the design of this museum will be a relevant solution. The results of this museum design include the development of interactive and participatory spaces that aim to build an interesting and immersive visitor experience. With a participatory space system, this museum is not only a collection storage place, but also a learning environment that allows visitors to be actively involved in creating new meanings and experiences. Apart from that, it is hoped that this museum can become a learning center that encourages innovation, creativity and development of the creative textile industry. The benefits of designing a Textile Museum in Bandung City include maintaining and preserving Indonesia's cultural heritage, increasing cultural awareness, strengthening local identity, as well as developing the education, tourism and economic sectors of local communities. Keywords: Museums, Textiles, Globalization, Interactive